Analysis of Maximum Profit From The Sale of Medan Floss Roll Using The Simplex Method And POM-QM Software - Gultom, Pesta; Artan, Silvia; Artan, Silvina (Economics and Digital Business Journal, 2025)
Abstract Shredded bread rolls are examples of some original culinary products from Eastern Indonesia, especially in the region of West Papua. This product can also be made by tourists visiting West Papua and it is possible to buy it for daily consumption whether it's breakfast, lunch, dinner, or snack. The purpose of establishing the business is to preserve the cultural values in the region and improve the regional economy, so that it is therefore necessary to have a technique or method in determining the maximum profit. The simplex method is the method used in this study and utilizes information technologyuse of POM-QM tools to calculate the estimated cost of selling and shipping the product.